Motivations for Volunteerism: Implications for Engagement and Recruitment (Journal of Organizational Psychology, 2020)
As demographics and volunteering interests evolve in the United States, nonprofit organizations are refining their engagement and recruitment strategies. This pilot study is uses a mixed method approach to uncover intrinsic motivators for volunteerism, asking 1) what are the primary motivations for individuals to volunteer?; and 2) what can be learned from these motivation factors to help an organization more effectively and efficiently engage and recruit new volunteers? This study suggests three motivations for volunteerism: personal gain, commitment to cause, and education. Considering these motivation factors may help nonprofit organizations provide new ways of engaging and recruiting volunteers.
Keywords: Organizational Psychology; nonprofit; not-for-profit; volunteer; volunteer engagement; volunteer recruitment; Recruitment